2009
DOI: 10.1111/j.1365-2702.2008.02778.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in documentation – a study of peripheral venous catheters

Abstract: Development of terms is needed to assure standardisation of postinsertion PVC documentation. Education of nurses on proper PVC documentation should be given priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…2006). A recent study shows that the PVC documentation performed by Swedish nurses was unsatisfactory and lacking in quality (Ahlqvist et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2006). A recent study shows that the PVC documentation performed by Swedish nurses was unsatisfactory and lacking in quality (Ahlqvist et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2006). Research indicates that PVC documentation among adult patients is scarce and that patient records are lacking information about insertion and removal in 30–50% of the inserted PVCs (Ahlqvist et al. 2006, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…2006, 2009b). Ahlqvist et al . (2009b) suggested that the development and implementation of standardised terms and guidelines for documenting PVCs are necessary to provide safe handling and control of PVCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lack of studies that analyze the quality of care records, regions punched and peripheral catheterrelated complications, this device is the most used in hospitals. Furthermore, the lack of knowledge and nursing protocols regarding the particularities of venous access in the elderly can greatly increase morbidity, hospitalization and hospital costs [14][15] .…”
Section: Management Of Complications Of Intravenous Therapymentioning
confidence: 99%